Molecularly Imprinted Electrochemical Sensors - Suryanarayanan, Vembu; Wu, Cheng-Tar; Ho, Kuo-Chuan (Electroanalysis (New York, N.Y.), 2010)
In this review, the applications of molecularly imprinted polymer (MIP) materials in the area of electrochemical sensors have been explored. The designs of the MIPs containing different polymers, their preparation and their immobilization on the transducer surface have been discussed. Further, the employment of various transducers containing the MIPs based on different electrochemical techniques for determining analytes has been assessed. In addition, the general protocols for getting the electrochemical signal based on the binding ability of analyte with the MIPs have been given. The review ends with describing scope and limitations of the above electrochemical based MIP sensors.